Selective molecular separation by interfacially crystallized covalent organic framework thin films - Dey, K.; Das, A; Mukherjee, R.; Kharul, U. K.; Banerjee, R. (Journal of the American Chemical Society, 2017)
Exponential interest in the field of covalent organic frameworks (COFs) stems from the direct correlation between their modular design principle and various interesting properties. However, existing synthetic approaches to realize this goal mainly result in insoluble and unprocessable powders, which severely restrict their widespread applicability. Therefore, developing a methodology for easy fabrication of these materials remains an alluring goal and a much desired objective. Herein, we have demonstrated a bottom-up interfacial crystallization strategy to fabricate these microcrystalline powders as large-scale thin films under ambient conditions. This unique design principle exploits liquid-liquid interface as a platform, allowing simultaneous control over crystallization and morphology of the framework structure. The thin films are grown without any support in free-standing form and can be transferred onto any desirable substrate. The porous (with Tp-Bpy showing highest SBET of 1a151 m2 g-1) and crystalline thin films, having high chemical as well as thermal stability, also hold the merit to tune the thickness as low as sub-100 nm. These nanostructured thin COF films demonstrate remarkable solvent-permeance and solute-rejection performance. A prominent instance is the Tp-Bpy thin film, which displays an unprecedented acetonitrile permeance of 339 L m-2 h-1 bar-1.